Histone Deacetylase Inhibition Attenuates Cardiomyocyte Hypoxia-Reoxygenation Injury - Williams, Aaron M.; He, Wei; Li, Yongqing; Bhatti, Umar F.; Nikolian, Vahagn C.; Chang, Panpan; Chang, Zhigang; Halaweish, Ihab; Liu, Baoling; Cheng, Xin; Alam, Hasan B. (Current Molecular Medicine, 2018)
Background: Cardiac reperfusion injury can have devastating consequences. Histone deacetylase (HDAC) inhibitors are potent cytoprotective agents, but their role in the prevention of cardiac injury remains ill-defined. Objective: We sought to determine the therapeutic potential of HDAC inhibitors in an in vitro model of cardiomyocyte hypoxia-reoxygenation (H/R). Method: H9c2 cardiomyocytes were subjected to H/R and treated with various classspecific and pan-HDAC inhibitors in equal concentrations (5μM). Biological activity of inhibitors was determined, as a proxy for concentration adequacy, by Western blot for acetylated histone H3 and α-tubulin. Cell viability and cytotoxicity were measured by methyl thiazolyl tetrazolium and lactate dehydrogenase assays, respectively. Mechanistic studies were performed to better define the effects of the most effective agent, Tubastatin-A (Tub-A), on the phosphoinositide 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) pathway effectors, and on the degree of autophagy. Results: All inhibitors acetylated well-known target proteins (histone H3 and α-tubulin), suggesting that concentrations were adequate to induce a biological effect. Improved cell viability and decreased cell cytotoxicity were noted in cardiomyocytes exposed to Tub-A, whereas the cytoprotective effects of other HDAC inhibitors were inconsistent. Pro-survival mediators in the PI3K/mTOR pathway were up-regulated and the degree of autophagy was significantly attenuated in cells that were treated with Tub-A. Conclusion: HDAC inhibitors improve cell viability in a model of cardiomyocyte H/R, with Class IIb inhibition (Tub-A) demonstrating superior cellular-level potency and effectiveness. This effect is, at least in part, related to an increased expression of prosurvival mediators and a decreased degree of autophagy.
Keywords: histone deacetylase inhibitors